Personalisasi Instrumen Pajak Karbon Melalui Skema Cap and Tax Sebagai Sarana Mereduksi Emisi Karbon di Indonesia - Santoso, Malvin; Lie, Gunardie (Peneliti.net, 2025)
Indonesia, one of the world's largest carbon emitters, ranked 10th globally in 2022, projecting emissions of 700 million tons per year, marking an 18.3% increase from the previous year. The primary sources of carbon emissions stem from fossil fuel consumption, followed by land use change and deforestation. This dependence on fossil fuels persists due to the nation's limited development of Renewable Energy (RE) sources. Consequently, the high carbon cycle contributes significantly to air pollution, exacerbating greenhouse gas effects, leading to extreme climate changes, global warming, polar ice melt, disease outbreaks, health complications, forest fires, and food scarcity worldwide. Recognizing the severity of these issues, Indonesia has committed to reducing fossil fuel usage and carbon emissions, aligning with international agreements such as the Paris Agreement, Sustainable Development Goals 2030, and Net Zero Emissions 2060, as articulated in the United Nations General Assembly. To enforce these commitments, Indonesia implements a Carbon Tax as a Pigovian tax (Polluter Pays Principle) under environmental law, regulated by Law Number 7 of 2021 on Tax Harmonization and Presidential Regulation Number 98 of 2021 on Carbon Economic Value. This mechanism supports the establishment of Cap and Tax initiatives in Indonesia. Qualitative descriptive research reveals Indonesia's adoption of a combined carbon trading scheme modeled after those in several European Union countries, aiming for broader societal acceptance.